2022
DOI: 10.3390/ncrna8050068
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Treatment Modulates Long Non-Coding RNA Isoforms Expression in Human Cells

Abstract: Long noncoding RNAs (lncRNAs) undergo splicing and have multiple transcribed isoforms. Nevertheless, for lncRNAs, as well as for mRNA, measurements of expression are routinely performed only at the gene level. Metformin is the first-line oral therapy for type 2 diabetes mellitus and other metabolic diseases. However, its mechanism of action remains not thoroughly explained. Transcriptomic analyses using metformin in different cell types reveal that only protein-coding genes are considered. We aimed to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…How metformin acts on lncRNAs is not clear; a bioinformatics study showed that metformin promotes different expressions of lncRNA isoforms among lung cells, kidney cells, embryonic cells, hepatocytes, and pancreatic cells. For example, NEAT1-202, the canonical isoform of the NEAT1 gene, is upregulated in five out of six cell lines by metformin treatment, but other isoforms showed different fold change directions ( Conceicao et al, 2022 ). This may explain different results for the same lncRNA in different studies.…”
Section: Metformin Mediates Lncrna Expressionsmentioning
confidence: 99%
“…How metformin acts on lncRNAs is not clear; a bioinformatics study showed that metformin promotes different expressions of lncRNA isoforms among lung cells, kidney cells, embryonic cells, hepatocytes, and pancreatic cells. For example, NEAT1-202, the canonical isoform of the NEAT1 gene, is upregulated in five out of six cell lines by metformin treatment, but other isoforms showed different fold change directions ( Conceicao et al, 2022 ). This may explain different results for the same lncRNA in different studies.…”
Section: Metformin Mediates Lncrna Expressionsmentioning
confidence: 99%